Water and nitrogen stress effects on canopy development and biomass allocation in fodder beet (Beta vulgaris L.). Issue 1 (2nd January 2022) - Khaembah, Edith N.; Maley, Shane; Gillespie, Richard; George, Mike; Michel, Alexandre J.; Chakwizira, Emmanuel; de Ruiter, John; Teixeira, Edmar
ABSTRACT: The effects of water stress on fodder beet ( Beta vulgaris L.) production in the field are confounded by the influences of variable inter- and intra-season rainfall. In this study, a rain shelter experiment investigated the effect of water and nitrogen (N) stress on dry matter (DM) production, DM allocation and N partitioning in fodder beet ('Rivage'). Two water-management treatments, irrigated (replacement of the profile water lost weekly) and unirrigated (limited water applied only during fertigation), and three fertiliser N treatments (0, 50 and 300 kg N ha −1 (hereafter, 0N, 50N, 300N)) were evaluated during the 2016–2017 season. Under irrigation, the yield was greater ( P  = .02) for the 50N than 0N treatments (29.4 and 24.9 t DM ha −1, respectively). Yield did not differ ( P  = .42) between irrigated 50N and 300N (30.6 t DM ha −1 ) treatments, indicating surplus N application to the latter. Water and N stress restricted leaf growth, lowered N uptake and reduced yield by 48%–51%. Surplus N in irrigated 300N treatments resulted in increased N uptake and leaf proportion but reduced the storage root proportion. These results demonstrate the plasticity of fodder beet biomass and N allocation in adapting to the availability of water and N.